Bridging divided worlds : - Carroll, Jackson W. (Jossey-Bass, 2002)
Bridging Divided Worlds by Jackson W. Carroll and Wade Clark Roof-- two experts in the field of contemporary religion-- presents a comprehensive study of generational dynamics within congregations. Their groundbreaking work analyzes the crucial role the generations play in reshaping the American religious landscape. Throughout the book the authors examine current religious and spiritual trends and reveal how these changes can offer opportunities for enriching a congregation's faith and spiritual life.